Kualitas Produk dan Citra Merek sebagai Faktor yang Mempengaruhi Keputusan Pembelian Kopi Suki di Kecamatan Sidikalang Kabupaten Dairi - Christin C. Sitorus; Khafi Puddin (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of product quality and brand image on purchasing decisions for Kopi Suki products in Sidikalang District, Dairi Regency. The research method used is quantitative with a survey approach through the distribution of questionnaires to 94 Kopi Suki consumers selected as samples. Data were analyzed using multiple linear regression with the help of SPSS version 30.0. The results showed that product quality has a positive and significant effect on purchasing decisions with a regression coefficient of 0.409 and a significance value of 0.000. Brand image was also proven to have a positive and significant effect with a regression coefficient of 0.592 and a significance value of 0.000. Simultaneously, both variables have a significant effect on purchasing decisions with a coefficient of determination (R²) of 0.870, which means that 87% of the variation in purchasing decisions can be explained by product quality and brand image. These findings indicate that consistent improvement in product quality and strengthening a positive brand image are very important for Kopi Suki businesses to increase consumer loyalty and expand market share.